Histopathological alterations of the parathyroid glands in haemodialysis patients with secondary hyperparathyroidism refractory to cinacalcet hydrochloride. Issue 9 (12th May 2011) - Sumida, Keiichi; Nakamura, Michio; Ubara, Yoshifumi; Marui, Yuji; Tanaka, Kiho; Takaichi, Kenmei; Tomikawa, Shinji; Inoshita, Naoko; Ohashi, Kenichi
Abstract : Background: Cinacalcet treatment for secondary hyperparathyroidism (SHPT) has demonstrated parathyroid size regression and morphological changes, such as cystic degeneration and hypovascularisation, on ultrasonography.; However, there have been very few reports regarding the histopathological alterations of hyperplastic parathyroid glands in patients with SHPT after administration of cinacalcet. The aim of this study was to elucidate the effects of cinacalcet for histopathological alterations on the parathyroid glands. Methods: A total of 92 hyperplastic parathyroid glands were obtained from 24 dialysis patients with severe SHPT who underwent total parathyroidectomy and were enrolled in this study. Patients were divided into those treated with and without cinacalcet (cinacalcet group and conventional group, respectively; both n=12). The areas of oxyphil cells, cystic degeneration, haemorrhagic changes and haemosiderin deposition were assessed semiquantitatively. Results: Total maximal parathyroid gland weight and maximal-to-minimal parathyroid gland weight ratio were significantly higher in the cinacalcet group compared with the conventional group (1798.7±1658.3 mg vs 764.2±471.1 mg, p=0.018, 15.8±13.9 vs p=0.047, 6.6±4.2, respectively). Significant increases were observed in oxyphil cell area (61.7%±17.1% vs 36.7%±15.6%, p=0.001) and haemosiderosis score (1.50±1.24 vs 0.42±0.51, p=0.029) in the former rather than the latter group. Conclusions: These results suggest that cinacalcet may induce specific qualitative alterations of hyperplastic parathyroid glands in patients with severe SHPT.